2012
DOI: 10.1016/j.placenta.2012.05.012
|View full text |Cite|
|
Sign up to set email alerts
|

First trimester screening of maternal placental protein 13 for predicting preeclampsia and small for gestational age: In-house study and systematic review

Abstract: Objective: To describe normative levels of PP13 in first-trimester of pregnancy and determine the accuracy of PP13 in predicting preeclampsia and small for gestational age (SGA) infants.Methods: We measured PP13 in archived first trimester serum samples from an unselected maternal cohort of 2,989 women. Associations of PP13 levels and diagnostic accuracy in predicting adverse pregnancy outcomes were assessed using multivariate logistic regression models. Due to inadequate number of cases we then conducted a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Previous studies on the predictive properties of PP-13 for pre-eclampsia and SGA yielded conflicting results. While some studies found significantly lower first-trimester levels of PP-13 in pregnancy complicated by pre-eclampsia [3,6,10,[12][13][14]29] or SGA [6,15,29] suggesting a potential incorporation of this biomarker in the risk assessment for pre-eclampsia, especially for the early-onset form [3,10], other cohorts and case-control studies failed to find such associations [16][17][18][19]. Moreover, even when a significant association is found, the predictive accuracy varies, with some studies showing promising results [3,6,[10][11][12] and others showing less remarkable predictive properties [13-15, 24, 29].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on the predictive properties of PP-13 for pre-eclampsia and SGA yielded conflicting results. While some studies found significantly lower first-trimester levels of PP-13 in pregnancy complicated by pre-eclampsia [3,6,10,[12][13][14]29] or SGA [6,15,29] suggesting a potential incorporation of this biomarker in the risk assessment for pre-eclampsia, especially for the early-onset form [3,10], other cohorts and case-control studies failed to find such associations [16][17][18][19]. Moreover, even when a significant association is found, the predictive accuracy varies, with some studies showing promising results [3,6,[10][11][12] and others showing less remarkable predictive properties [13-15, 24, 29].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, even when a significant association is found, the predictive accuracy varies, with some studies showing promising results [3,6,[10][11][12] and others showing less remarkable predictive properties [13-15, 24, 29]. In their systematic review and meta-analysis of 8 studies, Schneuer et al reported sensitivity rates of 24% and 45% for pre-eclampsia and early-onset pre-eclampsia, respectively, at 5% false positive rate [29]. In a more recent metaanalysis of 19 studies, the detection rate ranged from 47% for all cases of pre-eclampsia to 83% for early cases alone, at a 10% false positive rate [30].…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenic markers are most promising, particularly PlGF and sFlt‐1. Of the placental proteins, PP‐13 and PAPP‐A were associated most consistently with pre‐eclampsia. Large prospective studies using biomarkers are expensive, and most existing data are on markers obtained routinely during fetal anomaly screening.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the conclusions of a recent systematic review, which found significant variability in the performance of this analyte and concluded that, despite early promising data, it does not appear that PP13 is of clinical utility. 49 …”
Section: Discussionmentioning
confidence: 99%